Experiments on the relative mobility of mudflow as submarine slide simulation using lock-exchange system - Haza, Z.F. (2011)
This paper has intention to inspect the behavior of gravity flows moving on beds in order to simulate the phenomenon of submarine slide. This objective is implemented by performing laboratory experiment using rectangular glass channel. The full-depth lock-exchange system and an image analysis technique are applied to measure the distance-time advancement of the gravity flows formation. A two-chamber material of mud and water is used to generate gravity flows. The model takes into account the kaolin clay content percentage of mud and the mixing region due to interaction between mud and water. Several tests are run to calibrate an entrainment parameter in order to reproduce gravity currents moving on sloping beds. The comparison between numerical and experimental results shows that the developed model is a valid tool to reproduce gravity current's dynamics.